A Mixed-Methods Approach for Embedding Cost Analysis Within Fidelity Assessment in School-Based Programs. (May 2023) - Bradshaw, Catherine P.; Debnam, Katrina J.; Player, Daniel; Bowden, Brooks; Lindstrom Johnson, Sarah
This mixed-methods study describes a framework for conducting cost analyses of school-based programs leveraging fidelity data and applying the ingredients method. We illustrate this approach by applying it to Positive Behavioral Interventions and Supports (PBIS), drawing on multiple sources of data from a sample of U.S. 77 schools that were trained in PBIS. We concluded that the average per school cost of PBIS was US53, 216.00 (median = US36, 698), with an average per-pupil cost of US90.00 (median = US58.00), which is considerably less than other school-based prevention models. The cost did, however, differ by implementation level, such that high-fidelity implementation tended to cost more than low-fidelity implementation. We provide a case illustration to elucidate some of the cost drivers of PBIS implementation. Specifically, these data highlight the variability in the amount of training and coaching by the specific evidence-based program implemented within the tiered PBIS framework. Through this case illustration, we demonstrate the utility of tracking costs of school-based program within the context of fidelity data collection. The findings also suggest the potential cost savings of PBIS, both when compared with other evidence-based interventions as well as the known costs of negative school outcomes like dropout.